Parenting stress during the Covid-19 pandemic era: A literature review - Indah Rizky Valiant; Elsye Maria Rosa (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Anxiety, stress and depression in parents occur due to Covid-19 and Lockdown. The mental health of the parents has an impact on the child care they do. The aim of this literature review is to synthesize the best available evidence about parenting stress in the era of the COVID-19 pandemic. This literature review useds 4 databases, namely Pubmed, Ebsco, ScienceDirect and Google Scholar. The inclusion criteria, used in the selection of this study were full text, articles or journals in English, topics about parenting during Covid-19 pandemic era and articles or journals for the last 2 years (2019-2021). NVivo with NVivo 11 plus software were used for data analysis. Eleven journals were obtained based on the screening process and reviewed in this literature. The results of the analysis obtained 3 major themes, namely stressors of parenting in covid-19, parental stress and parenting stress, child abuse and child stress. Support is needed for parents during the Covid-19 pandemic so that parents do not experience stress and provide positive care for their children.